Nightmare on Dendropanax Street: What is Dendropanax arboreus (Araliaceae)? - Morales, J. Francisco; Idárraga-Piedrahita, Alvaro (Phytotaxa, 2022)
Dendropanax arboreus have been considered a high phenotypic variable species and the name applied to many different entities from Mexico and the West Indies to Brazil and Bolivia, from sea level up to 3200 m. A circumscription of D. arboreus based on the West Indies populations is proposed. This is the first step in order to delucidate how many taxa have been lumped into the synonymy of that species in the Neotropic. Lectotypes are designated for the names Gilibertia brachypoda and Sciodaphyllum samydifolium.